Disrupted metabolic signatures in amniotic fluid associated with increased risk of intestinal inflammation in cesarean section offspring - Liu, Yongjie; Zhang, Jun; Feng, Liping (Frontiers in Immunology, 2023)
Children born by cesarean section (CS) are at a greater risk of inflammatory bowel disease (IBD). However, the mechanisms underlying the association are not yet well understood. Herein, we investigated the impact of CS delivery on colonic inflammation and mechanisms underlying these effects in offspring. CS mice model and dextran sulfate sodium (DSS)-induced colitis model were constructed and used to analyze the impact of CS on the development of colitis. Colonic tight junction markers and epithelium differentiation markers were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). Levels of zonulin in serum were detected by enzyme-linked immunosorbent assay (ELISA). Immune cells in colon were analyzed by flow cytometry. Metabolic profiling between human vaginal delivery (VD) and CS AF were analyzed by using mass spectrometry. Transcriptome changes between VD AF- and CS AF-treated human intestine epithelial cells were analyzed by RNA-sequencing. A multi-omics approach that integrated transcriptomics with metabolomics to identify the pathways underlying colonic inflammation associated with delivery modes. Then, the identified pathways were confirmed by immunoblotting and ELISA. Mice pups delivered by CS exhibited a defective intestinal homeostasis manifested by decreased expression of tight junction markers of ZO-1 and Occludin in the colons, increased levels of zonulin in serum and dysregulated expression of intestinal epithelium differentiation markers of Lysozyme, Mucin2, and Dipeptidyl peptidase-4. CS pups were more susceptible to DSS-induced colitis compared to VD pups. The proportion of macrophage, dendritic cells (DCs), and natural killer cells (NKs) in the colons were altered in an age-dependent manner compared with pups born naturally. The metabolites in AF differed between CS and VD cases, and the CS AF-induced differentially expressed genes (DEGs) were significantly enriched in pathways underlying IBD. Signal transducer and activator of transcription 3 (STAT3) signaling was downregulated in NCM460 intestinal epithelial cells by CS AF compared to VD AF and in colon of CS pups compared to VD pups. Deficiency in metabolites like vitamin D2 glucosiduronate in CS AF may attribute to the risk of inflammatory intestine through STAT3 signaling. Our study provides a novel insight into the underlying mechanisms of CS-associated intestinal inflammation and potential prevention strategies.